Антропологічний склад населення давньоруських міст Середнього Подніпров’я - Рудич, Т.О. (Археологія, 2012)
Поповнення палеоантропологічних джерел дозволяє дещо поновому оцінити склад населення давньоруських міст Середнього Подніпров’я. Проанализированный антропологический материал из раскопок городских могильников ХІ—ХІІІ вв. Среднего Поднепровья подтверждает выводы о принадлежности населения к европеоидной расе, его неоднородности при доминировании в городах славянского компонента. Новый материал позволяет уточнить вопрос о происхождении выходцев из круга славянских популяций в составе горожан. Он свидетельствует, что мезодолихокранный среднелицый (с тенденцией к узколицести) тип, характеризующий сельские популяции территории полян, на городских могильниках Среднего Поднепровья не является доминирующим. Он характеризует женские серии из Родни, отдельные могильники Чернигова и фиксируется в Киеве. Analysis of anthropological material from excavations of the 11th—13th c. city cemeteries in the Dnipro River middle region confirms conclusions that the population belonged to the European race and was multivendor with Slavonic component dominating in the cities. The new material allows the author to specify the issue of origin of Slavs in city population structure. This material testifies that mesodolichocranic middlefaced type (with tendency to narrowfaced type) which is peculiar for rural populations of the Polyans’ areas does not dominate in city cemeteries of the Dnipro River middle region. Women’s series from Roden and some Chernihiv cemeteries are characterized by this type, it is also recorded in Kyiv.